Anti-breast cancer triterpenoid saponins from the thorns of Gleditsia sinensis. Issue 16 (18th August 2019) - Yu, Jinqian; Li, Gang; Mu, Yan; Zhou, Honglei; Wang, Xiao; Yang, Peng
Abstract: One new triterpenoid saponin (1 ), as well as six known ones (2–7 ), were isolated from the ethanol extract of the thorns of Gleditsia sinensis . Their structures were elucidated by extensive spectroscopic analysis in conjunction with chemical evidence. Cytotoxic activity of compounds1–6 was evaluated against human breast cancer MCF 7 cells in vitro by the MTT method. Our results revealed moderate activities for compounds1–6 with IC50 values of 18.43, 30.47, 18.46, 10.02, 30.76, and 17.32 μM, respectively. Furthermore, compounds1, 3, 4, and6 induced apoptosis in MCF 7 cell, with1 and6 causing late apoptosis of MCF 7 cells, while3 and4 acting oppositely. Abstract :